Development of nuclear and mitochondrial microsatellite markers for the relictual conifer genus Athrotaxis (Cupressaceae) - Sakaguchi, Shota; Worth, James R. P.; Jordan, Gregory J.; Thomas, Philip; Ito, Motomi (Conservation genetics resources, 2015)
Athrotaxis D. Don (Cupressaceae) is a relictual conifer genus and is comprised of two or three ecologically divergent species endemic to Tasmania. Utilizing RNA-seq data obtained by next generation sequencing techniques, 16 polymorphic EST-SSR (simple sequence repeats in expressed sequence tags) markers with 2–15 alleles in nuclear and mitochondria genomes were developed and characterized. These markers will be used to investigate the speciation and hybridisation processes in the genus, the species’ range-wide genetic structure and diversity and the importance of clonality in maintaining current populations.